Relationship between Dysmenorrhea, Dietary Inflammatory Index, and C-reactive Protein Level - Mucuk, Salime; Yılmaz, Müge; Onur, Aslı (Progress in Nutrition, 2022)
Aim: Primary dysmenorrhea is a common health problem that affects women's quality of life. This study aimed to determine the relationship between dysmenorrhea, dietary inflammatory index (DII), and C-reactive protein (CRP) serum levels. Study Design: This cross-sectional study was conducted between March and June 2019 with 106 university students, including 56 with primary dysmenorrhea and 50 without dysmenorrhea. The data were collected via a survey form including questions about the participants’ socio-demographic characteristics and obstetric/gynecological histories, the Healthy Lifestyle Behaviors Scale II (HLBS-II), and the Visual Analog Scale (VAS). Anthropometric measurements of the participants were performed, their three-day food consumption record was received, their DII scores were calculated, and their CRP level was measured. The independent samples t-test and Mann-Whitney U test were used to compare the participants’ DII scores and CRP levels. A linear regression analysis was performed to determine the relationship between dysmenorrhea, DII, and CRP level. A p-value of less than 0.05 was considered statistically significant. Results: The DII 3rd tertile mean score of the dysmenorrhea group (5.017 ± 1.231) was higher than that of the non-dysmenorrhea group (3.681 ± 1.309) (t=3.154, p=0.003). The median value of CRP was higher in the dysmenorrhea group [0.72 (0.37-1.65)] than in the non-dysmenorrhea group [(0.48 (0.23-1.21)] (z=2.117, p=0.034). According to the linear regression analysis, dysmenorrhea significantly increased the CRP value by 0.471 units compared to the non-dysmenorrhea group (β=0.471; p=0.038). Conclusion: Participants with dysmenorrhea had higher serum CRP levels and DII scores.